Spatial Dynamics of Mangrove Changes and Their Adaptive Capacity in Kandanghaur District, Indramayu Regency, West Java Province, Indonesia - Sodikin, Sodikin Sodikin; Fahmi, Fauzi; Astriyandi, Asep Andri; Husniyyah, Maitsa Zulfa (Program Pascasarjana Universitas Sriwijaya, 2024)
This study aims to analyze mangrove ecosystems' dynamics and adaptive capacity in the Kandanghaur District, Indramayu Regency. This research method uses a spatial approach, collecting mangrove distribution data by analyzing Google Earth satellite images from 2009, 2016, and 2023. Data on environmental characteristics, mangrove vegetation density, and mangrove species identification were collected through direct field ground checks using the line transect method. Data analysis techniques were applied by implementing the mangrove ecosystem's adaptive capacity formulation. The results show that mangroves in Kandanghaur District from 2009 to 2023 increased by 70.03 hectares, and the majority of mangroves are distributed along the coast, water channels, and community ponds with a silvofishery system. The adaptive capacity of mangroves in Kandanghaur District varies from low to high, with high adaptive capacity located in two villages, namely Ilir Village and Parean Girang Village, with adaptive capacity values of 0.66 and 0.63, respectively. Mangroves with medium adaptive capacity are in Bulak Village with an adaptive capacity value of 0.60, and mangroves with low adaptive capacity are in Eretan Wetan and Eretan Kulon Villages with an adaptive capacity of 0.40.